The Sequence Recall Task and Lexicality of Tone: Exploring Tone “Deafness” - Carlos Gussenhoven; Carlos Gussenhoven; Yu-An Lu; Sang-Im Lee-Kim; Chunhui Liu; Hamed Rahmani; Tomas Riad; Hatice Zora (Frontiers in Psychology, 2022)
Many perception and processing effects of the lexical status of tone have been found in behavioral, psycholinguistic, and neuroscientific research, often pitting varieties of tonal Chinese against non-tonal Germanic languages. While the linguistic and cognitive evidence for lexical tone is therefore beyond dispute, the word prosodic systems of many languages continue to escape the categorizations of typologists. One controversy concerns the existence of a typological class of “pitch accent languages,” another the underlying phonological nature of surface tone contrasts, which in some cases have been claimed to be metrical rather than tonal. We address the question whether the Sequence Recall Task (SRT), which has been shown to discriminate between languages with and without word stress, can distinguish languages with and without lexical tone. Using participants from non-tonal Indonesian, semi-tonal Swedish, and two varieties of tonal Mandarin, we ran SRTs with monosyllabic tonal contrasts to test the hypothesis that high performance in a tonal SRT indicates the lexical status of tone. An additional question concerned the extent to which accuracy scores depended on phonological and phonetic properties of a language’s tone system, like its complexity, the existence of an experimental contrast in a language’s phonology, and the phonetic salience of a contrast. The results suggest that a tonal SRT is not likely to discriminate between tonal and non-tonal languages within a typologically varied group, because of the effects of specific properties of their tone systems. Future research should therefore address the first hypothesis with participants from otherwise similar tonal and non-tonal varieties of the same language, where results from a tonal SRT may make a useful contribution to the typological debate on word prosody.